Towards an understanding of the Structural Gap - Octavia Haure (JoSTrans: The Journal of Specialised Translation)
Although there is little dispute that languages differ at microstructural level, and although different thinking styles are acknowledged, little work seems to have been done on how this impacts on the written word – on the structure and form of a written text, and none with specific reference to texts in the field of the arts, film writing and reviews. Nor does there seem to be much information on how this impacts on translation procedures. Therefore my article is challenging the invariance requirement of retaining the broad macrostructure of text in order for the target reader to comprehend and appreciate the source text material correctly. This article presents some data from French and English film reviews, and in its capacity as a pilot study, is attempting to move towards an understanding of the structural gap between language macrostructures.